Elaborate harness buckles from Lori Berd - Devedjyan, Seda (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
Lori Berd with its necropolis and settlement belongs to the number of the most important Armenian archaeological sites as it reflects the history and development of the cultural peculiarities of North Armenia for almost two millennia – from the last centuries of the 3rd millennium BC up to the 6th -5th centuries BC.